Підготовка майбутніх учителів до розвитку критичного та дизайн-мислення молодших школярів у процесі вивчення обов’язкових психолого-педагогічних та вибіркових дисциплін - Тесленко Тетяна; Teslenko Tetiana; Сенчило Алла; Senchylo Alla; Мельнічук Неля; Melnichuk Nelya (Видавництво «Код», 2025)
Резюме. Описано досвід розвитку критичного та дизайн-мислення у здобувачів бакалаврського та магістерського рівня спеціальності А3 «Початкова освіта» у процесі фахової підготовки. Встановлено, що етапами розвитку дизайн-мислення є: емпатія, визначення проблеми, генерація ідей, створення прототипів та тестування. Наведено приклади роботи зі студентами на цих етапах під час вивчення обов’язкових («Педагогіка») і вибіркових освітніх компонентів («Розвиток критичного мислення молодших школярів», «Інфомайстерність: критичне мислення та медіаграмотність у педагогічній практиці», «Дизайн-мислення та розробка освітніх проєктів»).

Abstract. The article describes the experience of developing critical and design thinking in bachelor’s and master’s degree students majoring in A3 «Primary Education» in the process of professional training. The essence of these types of thinking and their role in forming future teachers’ ability to adapt, reflect, and creatively solve educational problems in the context of war in Ukraine are considered. It has been established that critical thinking is understood as the ability of an individual to analyze information, evaluate arguments, verify facts, and make informed conclusions. The essence of design thinking lies in the ability to solve problems using creative and innovative methods to create solutions that meet the needs of users. The stages of design thinking development are characterized as follows: empathy, problem definition, idea generation, prototyping, and testing. Examples are given of working with first-year (bachelor’s) students at these stages while studying compulsory («Pedagogy») and elective educational components («Development of Critical Thinking in Younger Schoolchildren», «Infomastery: Critical Thinking and Media Literacy in Pedagogical Practice»). The most effective tasks are those related to project implementation («Lesson in Shelter» with an emphasis on a safe educational environment); analysis of conflict situations from one’s own professional practice; selection of controversial questions and compilation of a checklist «How to ask controversial questions»; creation of a training course for teachers, a lesson plan for students (20–25 minutes) using discussion and controversial questions, etc. Detailed methodological guidelines for teachers and students when studying the topic «Media literacy of primary school teachers in the context of critical thinking» were provided. Emphasis is placed on the exercise «Analysis of information sources: truth or manipulation?», which teaches future teachers to analyze their media space and consciously approach issues of their own media consumption and prepare students for this. The advantages of the elective course for master’s level students «Design Thinking and Development of Educational Projects» in the context of the stated issues are described. Examples of classes with tasks for setting the main goals of forming a unique selling proposition, working with financial calculations for different budgets, proposing solutions and determining the uniqueness of one’s own product and creating its prototype («My Children’s Project. Space for Learning English», games with elements of meditation «Relax Quest», etc.), improving the brand and its positioning.
Preparation of future teachers for developing critical and design thinking of primary school students in the process of studying compulsory psychopedagogical and elective courses
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-15
Keywords: фахова підготовка майбутніх учителів початкової школи; «Педагогіка»; критичне та дизайн-мислення; безпечне освітнє середовище; медіаграмотність; інфомайстерність